Kombinasi Rasa Lemon Curd dan Cassava Tart dalam Kreasi Kue pada Cafe U.Berkopi - D. Zahra Adelia; Diah Banyuni (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
This study discusses the development of a food product called Cassava Tart with Lemon Curd and Butterfly Pea Pannacotta, aimed at reducing the use of imported wheat flour by utilizing mocaf (Modified Cassava Flour) as a local ingredient. The pannacotta, prepared with butterfly pea powder, adds color variation and appeal. Collaboration with the cafe U.berkopi was conducted to test product preference, involving 25 panelists in a hedonic test. The results showed that 100% of the panelists were very fond of the appearance and color, 80% were very fond of the aroma, 84% were very fond of the texture, and 92% were very fond of the taste. The standard recipe for this product consists of various ingredients, including mocaf flour, margarine, lemon juice, whipping cream, and sugar. Business analysis indicated a potential profit of Rp. 2,000,000 per month from the sale of 486 pieces. This study recommends that culinary innovation continue to be developed by utilizing local raw materials.